IMPLEMENTASI KEBIJAKAN PENDIDIKAN TINGGI: PELAKSANAAN REFORMASI PENDIDIKAN TINGGI DI INDONESIA - Daelami Ahmad Daelami Ahmad (LPPM STIA Banten, 2016)
Education policy is public policy, and is one of the state policies that serve as a guide to decision-making in the field of legal education-neutral and adapted to the environment. Along with the reform era and regional autonomy, education policy direction generally directed towards the decentralization of education. Government policy in the field of higher education stipulated in Law No. 12 of 2012 on Higher Education. Law No. 12 of 2012 was a response to the problems of higher education both micro and macro. The important thing was carried in the law is the governance of the college and university autonomy. Crucial issues that arise from this law lies in: the autonomy of higher education and liberalization of education, government responsibility, etatisme, half-hearted implementation of decentralization, autonomy restrictions, and commercialization of college. In the implementation of higher education policy implementation, the Government encourages the implementation of governance better colleges and universities autonomy in accordance with the rules, norms, and the main purpose of education.